Penerapan Komunikasi Efektif Pada Ny. D Sebagai Upaya Peningkatan Keteraturan ANC (Antenatal Care) - Reni Ardila; Nova Yulita (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2024)
Antenatal Care (ANC) is a preventive care health facility that was developed with the aim of  preventing and reducing complications for pregnant women. This research uses a descriptive type with an approach through a case study conducted on Mrs. D. This research was carried out at PMB Nila Trisnawati which is located on Jl. Tenayan, sail, kec. Tenayan Raya, Pekanbaru city. The data collection techniques used in this research are primary data and secondary data obtained from the results of interviews, observations, and physical examinations. This research aims to implement effective communication to increase the regularity of ANC visits and to determine the factors which influences ANC irregularities in pregnant women. The results of this research are that mothers’ knowledge increases and pregnant women come back for ANC checks from health workers. With this activity, it is hoped that pregnant women will continue to pay attention to their health.